Static Behavioral Studies of a 2D Taper Beam using Finite Elements Comprised of Functionally Graded Materials - Sunnam Nagaraju; K Naga Suresh; P Nagendra Babu; P Anil Kumar Reddy; JM Babu; N Prabhu Kishore (MATEC Web of Conferences, 2024)
The study examines the thermal and structural properties of beams made of functionally graded materials (FGMs) using the Finite Element Analysis (FEA) method and Reddy’s beam theory. The distribution of material qualities in thickness and length directions is influenced by mechanical and thermal loads. We calculate the stress and deflection of FG beams with a uniform load distribution. Quantitative results demonstrating the effects of multiple factors are provided by the Fusion 360 software. These include the change from alumina (ceramic) to aluminum (metal), boundary conditions, volume fraction distribution, and geometric features.